A Review on Fluid Flow and Mixing in Microchannel and their Design and Manufacture for Microfluidic Applications - Sarma, Pranjal; Patowari, Promod K. (Micro and Nanosystems, 2023)
The present time has witnessed a never-before-heard interest in and applications of microfluidic devices and systems. In microfluidic systems, fluid flows and is manipulated in microchannels. Mixing is one of the most important criteria for a majority of microfluidic systems, whose laminar nature hinders the efficiency of micromixing. The interface between the flowing fluid and the inner wall surface of the microchannel greatly influences the behaviour of fluidic flow in microfluidics. Many researchers have tried to pattern the surface, introduce obstacles to flow, and include micro- or nanoprotruded structures to enhance the mixing efficiency by manipulating the microchannel flow. New and rapid advances in MEMS and micro/nanofabrication technologies have enabled researchers to experiment with increasingly complex designs, enabling rapid transformation and dissemination of new knowledge in the field of microfluidics. Here, we report the fluid flow characteristics, mixing, and associated phenomena about microfluidic systems. Microfluidic systems and components such as microreactors, micromixers, and microchannels are reviewed in this work. We review active and passive micromixers, with a primary focus on widely used passive micromixers. Various microchannel geometries and their features, mixing efficiencies, numerical analysis, and fabrication methods are reviewed. Applications as well as possible future trends and advancements in this field, are included too. It is expected to make the reader curious and more familiar with the interesting field of microfluidics.
Keywords: micromixing